Phaeochromocytoma Mimicking Scleroderma - Joan Joo-Ching Khoo; Edward John Pratt (International Journal of Endocrinology)
We describe a patient with adrenal phaeochromocytoma who presented with peripheral vasospasm and ischaemia and other manifestations mimicking features of systemic sclerosis, which resolved after resection of the tumor. Phaeochromocytoma should be suspected in patients with features of scleroderma who are negative for auto-antibodies.